MENETAP ATAU PERGI? ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TURNOVER INTENTION KARYAWAN OUTSOURCING PRODUKSI PADA SALAH SATU PERUSAHAAN MANUFAKTUR DI KOTA GRESIK - Fakhri Octavian Kusdardjanto; Sulastri Irbayuni; Sugito (MANAJEMEN DEWANTARA, 2025)
This study aims to analyze the effect of job insecurity and job satisfaction on turnover intention among outsourced employees in the production division of a manufacturing company in Gresik. High turnover intention is a serious problem for companies because it can disrupt operational stability. By understanding the triggering factors, companies are expected to be able to take strategic steps to retain their employees. This study employs a quantitative approach with an associative research design. Data was collected from 80 respondents, who are outsourced production employees at the company, through a questionnaire. Data analysis was conducted using the Smart Partial Least Squares (PLS) application. The results of this study indicate that job insecurity is the main factor driving employees to consider changing jobs. When employees feel a high level of uncertainty about the continuity of their jobs, they are more likely to seek employment opportunities elsewhere. Conversely, job satisfaction plays a crucial role in retaining employees. The higher the level of satisfaction employees feel toward their jobs, the stronger their commitment to remain with the company.